PENGARUH KEEFEKTIFAN PENGENDALIAN INTERN, REWARD DAN MORALITAS INDIVIDU PADA PERILAKU TIDAK ETIS KARYAWAN (STUDI CV. SINAR DIAN) - Bellyanti, Luh Anggi; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2016)
The purpose of this study was to examine how the effectiveness of internal control, reward and individual morality against unethical behavior of employees. This research was conducted at the company's CV. Sinar Dian, the samples used were taken as many as 55 people using a quantitative approach in the form of associative. Data were collected by questionnaires and analysis techniques used are multiple regression. Results showed that the effectiveness of internal control, reward and negatively affect the individual morality of unethical behavior of employees
Keywords: The effectiveness of internal control, reward, individual morality